Metal‐Free Electrochemical Synthesis of Sulfonamides Directly from (Hetero)arenes, SO(2), and Amines - Blum, Stephan P. (Angew Chem Int Ed Engl, 2021)
Sulfonamides are among the most important chemical motifs in pharmaceuticals and agrochemicals. However, there is no methodology to directly introduce the sulfonamide group to a non‐prefunctionalized aromatic compound. Herein, we present the first dehydrogenative electrochemical sulfonamide synthesis protocol by exploiting the inherent reactivity of (hetero)arenes in a highly convergent reaction with SO(2) and amines via amidosulfinate intermediate. The amidosulfinate serves a dual role as reactant and supporting electrolyte. Direct anodic oxidation of the aromatic compound triggers the reaction, followed by nucleophilic attack of the amidosulfinate. Boron‐doped diamond (BDD) electrodes and a HFIP–MeCN solvent mixture enable selective formation of the sulfonamides. In total, 36 examples are demonstrated with yields up to 85 %.